Examination of Health Literacy Levels of Pre-Service Teachers - Didem Kilic; Guntay Tasci; Bahattin Deniz Altunoglu (Journal of Education in Science, Environment and Health)
Low level of health literacy causes a decrease in quality of life and social inequalities. Adequate health literacy levels of pre-service teachers will not only reduce the risk of disease, but also will contribute to development of a healthy lifestyle for societies. In the study, it is aimed to determine the health literacy levels of pre-service teachers, and to reveal how it changes in terms of various socio-demographic characteristics. The study group of the research consists of 482 pre-service teachers studying at the education faculties of state universities. The 'Turkey Health Literacy Scale-32' was used to determine the health literacy levels of the participants. In the analysis of the data parametric tests were used, since there were no outliers, and the normality assumptions were met. The results show that two-thirds (68%) of the research group have inadequate and limited health literacy. When health literacy index scores examined in terms of the variables discussed in the study, it is understood that the level of health literacy remains at a limited level. It is thought that making arrangements to improve health literacy in the curriculum of teacher training programs will directly contribute to a healthier life for both individuals and societies